(untitled) (Research, Society and Development, 2020)
The holding of the Rio 2016 Olympic and Paralympic Games increased the Government’s concerns about sports results and stimulated a significant increase in public investments in sport. Although public funding has historically been the main source of funds for Brazilian sport, the Bolsa-Atleta Program has become the main source of income for Paralympic athletes. The objective of this study was to discuss whether funding through the “Bolsa-Atleta” Program influences the maintenance and improvement of sport results of Brazilian Paralympic athletes inserted within the program or not. Variables such as funding, sex, athlete’s initial grant, age at which the athlete began to receive a grant, and birthplace will be analysed as possible predictors of athletes’ permanence in the program. For this, it was verified, by means of multiple linear regression, whether variables such as funding, gender, athlete’s initial grant, age at which he started receiving grant and place of birth are predictors of the athlete’s permanence and evolution in the sport. The data pointed out a relationship between the value of the financing and, in some cases, the age of insertion in the program with the permanence and evolution in the elite sport. The higher the value of the grant, the longer the stay and the greater the chances of obtaining a sports result.